PEMBERDAYAAN MASYARAKAT PESISIR PEMANFAATAN MANGROVE Sonneratia alba SEBAGAI SELAI BUAH PEDADA DI DESA LHOK BUBON, ACEH BARAT - Ropita Ropita; Mohamad Gazali; Deri Anggraini; Selvi Mardalena; Farah Salsabila; Rina Syafitri; Zulfadhli Zulfadhli; Zuriat Zuriat; Irnu Al Farisi; Nabil Zurba; Endah Anisa Rahma; Rinawati Rinawati; Sri Wahyuni (Universitas Teuku Umar, 2022)
Mangrove forest play important role in coastal ecosystem. In other hand, mangrove have economical benefit as source of functional food. The aimed of this empowerment programme is to give knowledge and skill to coastal community of Lhok Bubon Aceh regarding Pedada fruit jam (Sonneratia alba). The method of empowerment includes did socialization, prepare raw material, and did training to coastal community of Lhok Bubon West Aceh. Based on the result shown that the coastal communities are consist of the women of Lhok Bubon coastal have spirit for learning and enthusiasm to follow the empowerment community programme. The expected in future, the coastal communities can be applied the technique of pedada fruit jam of S. alba in order to give them value added.